THE EVALUATION OF TASTE THRESHOLD FOR FOUR MAIN TASTES BETWEEN DIABETIC AND HEALTHY INDIVIDUALS - Gaphor, Shanaz Mohammad; Saeed, Raz A. (European Scientific Journal, ESJ, 2014)
Background: Diabetes mellitus is a metabolic condition which affects multiple organs. Serious systemic complications of diabetes mellitus has led to multiple signs and symptoms which has affected dental care. Aim of the study: To assess therelationship between taste thresholds in type 2 diabetics and non-diabetics patients for four basic taste modalities. Patients and Methods: This single-blind case-control study was implemented on hundred diabetic patients who visited diabetes and endocrine center in Sulaimani; and hundred healthy individuals who visitedPeramerd dental clinic, for detection of taste sensitivity for four primary tastes. Taste thresholds were detected by the whole mouth taste method and the use of five concentrations for each taste. Thus, the data were analyzed by Mann-Whitney U Test and Spearman’scorrelation coefficient. Results: Statistical analysis indicate taste threshold measured for each yielded normal range for all tastes in diabetic group(0.032molar for sucrose,0.032for NaCl, 0.001molar for citric acid and 0.00001molar for quinine hydrochloride) but there was a significant difference in the perception of sweet and salt taste between the two groups(P<0.05). Conclusions: Decreased sweet taste sensitivity may result in an increased preference for glucose in diabetic patients.